Lexical Competence in Teaching English in Non-Philological Education through Using Authentic Materials - Bunyod Kholiyorov (International Journal on Integrated Education, 2023)
Nowadays, the importance of improving lexical competence in teaching technical English is becoming relevant. Using authentic materials can be a supportive mechanism in non-philological English language teaching. This article focuses on the new approaches to material selection, design, and implementation mainly focused on supporting ideas.